Recruitment and Retention of Tech-Savvy Talent for AI in Agriculture: Challenges Faced by HR in Rural Agribusiness - Adelia Azzahra; Sherina Prahitaningtyas; Fahad Khan Afridi; Makinde Grace Olubisi (Politeknik Siber Cerdika Internasional, 2025)
The integration of AI in agriculture is transforming rural agribusinesses, offering solutions for increased productivity and sustainability. However, these agribusinesses face significant challenges in recruiting and retaining AI talent due to geographical limitations, limited career growth opportunities, and perceptions of technological constraints. This study investigates the factors impacting AI talent acquisition and retention within rural agribusinesses and explores practical strategies to address these challenges. Using a qualitative approach, data were collected from HR professionals across rural agribusinesses, focusing on their experiences and strategies for managing AI-driven recruitment and retention. Findings indicate that limited candidate pools, infrastructural constraints, and perceptions of limited professional growth pose significant barriers to attracting tech-savvy talent. Effective retention strategies identified include flexible work arrangements, skill development programs, and digital engagement platforms, all of which contribute to higher job satisfaction among AI professionals in rural settings. The study concludes that rural agribusinesses can enhance their talent acquisition by emphasizing the impact of AI in sustainable agriculture and by adapting digital recruitment strategies to target tech-driven professionals seeking purpose-oriented careers. These findings provide valuable insights for HR practitioners and policymakers aiming to bridge the digital divide in agriculture through improved AI talent management.